Diversity of culturable nocardioform actinomycetes from wastewater treatment plants in Spain and their role in the biodegradability of aromatic compounds. Issue 2 (17th January 2018) - Soler, Albert; García-Hernández, Jorge; Zornoza, Andrés; Alonso, José Luis
ABSTRACT: Currently, municipal and industrial wastewater treatment plants (WWTPs) are mainly focusing on reduction of biological oxygen demand and on the removal of nutrients. However, there are microorganisms that interfere with the process. In this environment, there is a large diversity of microorganisms that have not been studied in detail and that could provide real and practical solutions to the foaming problems. Among such microorganisms, Gram-positive actinomycete bacteria are of special interest because they are known for producing secondary metabolites as well as chemically diverse compounds and for their capacity to degrade recalcitrant pollutants. Three different media were chosen to isolate actinomycetes from 28 WWTPs in Spain. A total of 189 activated sludge samples were collected; 126 strains were isolated and identified to belong to 1 suborder, i.e. Corynebacterineae, and 7 genera, i.e. Corynebacterium, Dietzia, Gordonia, Mycobacterium, Rhodococcus, Tsukamurella and Williamsia . Furthermore, 71 strains were capable of biodegrading at least 1 aromatic product, and that 27 of them amplified for catA gene. The results of this research help us understand the complexity of the foam-forming microbial populations in Spain and it shows that WWTPs can be a good source of microorganisms that can degrade phenol or naphthalene.